(untitled) (Research, Society and Development, 2021)
We aimed to evaluate the histomorphometry and proteomic profile of the canine uterus during all stages of the reproductive cycle. Eighteen healthy female dogs had their estrous cycle identified by clinical evaluation, vaginal cytology, and serum progesterone levels, which were allocated to the proestrus (n=5), estrus (n=5), diestrus (n=5), and anestrus (n=3) groups. All were submitted to elective ovariosalpingohysterectomy, and the uteri were collected for histomorphometric measurement (Image J software). For proteomic analysis, fragments of the uterine horns were subjected to protein measurement (Bradford method) and extraction by 2D electrophoresis (PDquest software). The results showed that the diestrus promoted greater values of thickness in the uterine structures (μm): uterine wall (2,223.8±229.8), endometrium (819.7±109.1), and myometrium (1,392.6±294.2). Uterus showed a protein profile with good reproducibility per phase (pI: 3.5–9.0; PM: 24–150 KDa), with 11 spots in all phases. Despite the greatest histomorphometric changes in the diestrus, we observed a greater number of spots in the estrus (253±45), followed by the proestrus (185±21), diestrus (113±39), and anestrus (80±21). This finding showed probable participation of these proteins in the uterine preparation for receiving gametes for fertilization. Our results showed greater uterine thickness in the diestrus, and greater protein secretion in the estrus, contributing to the prospection of identification of proteins responsible for the biological reproduction processes.